Impacts of the work environment on internship supervision in Social Work - Lopes, Gessica dos Santos Machado; Lewgoy, Alzira Maria Baptista (Argumentum, 2022)
Abstract: This article debates the impacts, trends, and challenges of the work environment on internship and supervision in Social Work in the southern region of Brazil. The study results from bibliographic research on the annals of the National Meetings of Researchers in Social Work and Brazilian Congresses of Social Workers and from field research with the internship coordinators of Social Work courses of the Academic Training Units and Orientation and Professional Inspection of the Regional Councils of Social Work. Reconfigurations of the work environment interfere with internship and supervision, when taking into consideration the easing of professional training that has been intensified by increasingly flexible and precarious working conditions, fostered by outsourcing, employee turnover, intellectual impoverishment, and lack of professional competence.